KEANEKARAGAMAN VEGETASI ULTRABASA DI HUTAN LINDUNG NANGA-NANGA PAPALIA KOTA KENDARI - basrudin basrudin; La Ode Agus Sali Mando; Muh. Salman Alfaridzhi; Mariana Zainun (Jurusan Kehutanan -FHIL-UHO, 2024)
This research aimed to determine the ultra-basic vegetation diversity in the Nanga-Nanga Papalia Protected Forest, Kendari City, Southeast Sulawesi. The study was conducted in May to June 2023, covering an area of 42 hectares within the Nanga-Nanga Papalia Protected Forest. The sampling intensity was set at 5% over a study area of 2.1 hectares, resulting in 52 sampling plots arranged using the Line Transect method. The findings revealed that the ultra-basic vegetation diversity across all vegetation levels in the protected forest was classified as low, with values of 1.25 for trees, 1.22 for saplings, 1.27 for poles, and 1.13 for seedlings